Combined inhibition of Wee1 and Chk1 as a therapeutic strategy in multiple myeloma - Bruyer, Angélique; Dutrieux, Laure; de Boussac, Hugues; Martin, Thibaut; Chemlal, Djamila; Robert, Nicolas; Requirand, Guilhem; Cartron, Guillaume; Vincent, Laure; Herbaux, Charles; Lutzmann, Malik; Bret, Caroline; et al. (Frontiers in Oncology, 2023)
Multiple myeloma (MM) is a hematological malignancy characterized by an abnormal clonal proliferation of malignant plasma cells. Despite the introduction of novel agents that have significantly improved clinical outcome, most patients relapse and develop drug resistance. MM is characterized by genomic instability and a high level of replicative stress. In response to replicative and DNA damage stress, MM cells activate various DNA damage signaling pathways. In this study, we reported that high Chk1 and Wee1 expression is associated with poor outcome in independent cohorts of MM patients treated with high dose melphalan chemotherapy or anti-CD38 immunotherapy. Combined targeting of Chk1 and Wee1 demonstrates synergistic toxicities on MM cells and was associated with higher DNA double-strand break induction, as evidenced by an increased percentage of gH2AX positive cells subsequently leading to apoptosis. The therapeutic interest of Chk1/Wee1 inhibitors' combination was validated on primary MM cells of patients. The toxicity was specific of MM cells since normal bone marrow cells were not significantly affected. Using deconvolution approach, MM patients with high Chk1 expression exhibited a significant lower percentage of NK cells whereas patients with high Wee1 expression displayed a significant higher percentage of regulatory T cells in the bone marrow. These data emphasize that MM cell adaptation to replicative stress through Wee1 and Chk1 upregulation may decrease the activation of the cell-intrinsic innate immune response.Our study suggests that association of Chk1 and Wee1 inhibitors may represent a promising therapeutic approach in high-risk MM patients characterized by high Chk1 and Wee1 expression.